Experimental evaluation of dynamic performance of three-phase AC-DC PWM rectifier with PD-type-2 fuzzy neural network controller - Acikgoz, Hakan; Coteli, Resul; Dandil, Besir; Ata, Fikret (Inst Engineering Technology-Iet, 2019)
Diode and thyristor-based rectifier circuits have been widely used in the industry. Due to non-linear structures of these circuits, they draw non-sinusoidal current from AC network as well as cause a low power factor in the AC side. The DC-link voltage of rectifier is affected by the changes in AC network or by the load variations on the DC side. Pulse-width modulated (PWM) rectifiers can eliminate the mentioned power quality problems if they control properly. This study proposes a controller with an adaptive and robust structure based on proportional+derivative type-2 fuzzy neural network (PD-T2FNN) for DC-link voltage control of PWM rectifier. Dynamic performance of PWM rectifier using the proposed controller is evaluated via dSPACE based experimental setup under different operation conditions: set-point change, step load change in the DC side of the rectifier, set-point change under load and capacitive operation mode. The experimental results are given for traditional PD and proportional+integral and T2FNN controllers to validity performance of the proposed controller. Performances of controllers are evaluated regarding settling time, overshoot, steady-state error and total harmonic distortion. PWM rectifier with PD-T2FNN DC-link voltage controller has superior performance for all operating conditions according to performance criteria when compared with other controllers.
Keywords: fuzzy neural nets; PWM rectifiers; voltage control; AC-DC power convertors; PD control; three-phase AC-DC PWM rectifier; PD-type-2 fuzzy neural network controller; thyristor-based rectifier circuits; nonlinear structures; AC network; low power factor; AC side; DC side; pulse-width modulated rectifiers; adaptive structure; PD-T2FNN; DC-link voltage control; set-point change; step load change; T2FNN controllers; power quality problems